2021
DOI: 10.1038/s41598-021-81781-9
|View full text |Cite|
|
Sign up to set email alerts
|

Probing the floral developmental stages, bisexuality and sex reversions in castor (Ricinus communis L.)

Abstract: Castor (Ricinus communis L) is an ideal model species for sex mechanism studies in monoecious angiosperms, due to wide variations in sex expression. Sex reversion to monoecy in pistillate lines, along with labile sex expression, negatively influences hybrid seed purity. The study focuses on understanding the mechanisms of unisexual flower development, sex reversions and sex variations in castor, using various genotypes with distinct sex expression pattern. Male and female flowers had 8 and 12 developmental sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Sex reversions may be early, late and can occur at lower or higher than quarternary orders of spikes (Shifriss 1960;Gopani et al, 1969). Sex reversion and high sexual polymorphisms in castor are due to temperature dependent alterations in oral developmental pathways (Sujatha et al 2021). Earlier studies have concluded that, the pistillateness in NES type is controlled by homozygous recessive genes (N-type) but contain environment sensitive (temperature > 32 0 C, high diurnal range of temperature, relative humidity, nitrogen, soil depth, age of the plant etc.)…”
Section: Sex Expressionmentioning
confidence: 99%
“…Sex reversions may be early, late and can occur at lower or higher than quarternary orders of spikes (Shifriss 1960;Gopani et al, 1969). Sex reversion and high sexual polymorphisms in castor are due to temperature dependent alterations in oral developmental pathways (Sujatha et al 2021). Earlier studies have concluded that, the pistillateness in NES type is controlled by homozygous recessive genes (N-type) but contain environment sensitive (temperature > 32 0 C, high diurnal range of temperature, relative humidity, nitrogen, soil depth, age of the plant etc.)…”
Section: Sex Expressionmentioning
confidence: 99%
“…For example, high temperature can induce the male development of plants [9]. Season, temperature, photoperiod, light, age of the plant, nutrient level, vegetative activity, pruning, and plant hormones are examples of environmental and intrinsic elements that have an impact on the expression of sex in castor [6,[10][11][12]. Despite significant advancements, the aforementioned ideas remain vulnerable in the lack of cytological data, and little is known about the molecular mechanisms underlying sex variation and the genes responsible for sex expression in castor.…”
Section: Introductionmentioning
confidence: 99%